Psychological and Physical Well-Being in Women Diagnosed with Breast Cancer: A Comprehensive Study of Anxiety, Depression, Sleep Quality, Physical Activity, and Sociodemographic Factors - Czech, Oliver J.; Matkowski, Rafał; Skórniak, Jakub; Malicka, Iwona (Medical science monitor, 2024)
BACKGROUND The psychophysical state of breast cancer patients impacts several outcomes and parameters and can directly affect diagnosis, prehabilitation, and treatment. This questionnaire-based study aimed to compare anxiety levels, depression, physical activity, sleep quality, and sociodemographic features in women with breast cancer and healthy women at a breast cancer unit in Poland. MATERIAL AND METHODS The study enrolled 41 breast cancer patients with no proposed treatment or psychological disorder diagnosis and 50 healthy volunteers. After enrolment, the subjects completed the Spielberger State-Trait Anxiety Inventory (STAI), Beck's Depression Inventory (BDI), International Physical Activity Questionnaire (IPAQ), Pittsburgh Sleep Quality Index (PSQI), and a sociodemographic questionnaire. RESULTS In this study, anxiety levels measured by the STAI anxiety subscale (56.05 [9.18] vs 37.62 [8.35], P<0.001) and BDI-assessed depression levels were higher in the cancer group (12.34 [6.26] vs 6.68 [6.36], P<0.001). PSQI measured quality of sleep (QOS) (5.80 [3.44] vs 3.76 [3.35], p=0.003) and physical activity (PA) levels evaluated by IPAQ were lower for breast cancer patients (1684.62 [2401.19] vs 3473.44 [4756.78], P=0.042). CONCLUSIONS Anxiety, depression, poor quality of sleep, and insufficient PA were common in breast cancer patients. The occurrence of cancer was the main factor causing mental health deterioration in patients with breast cancer. Also, mental state and well-being differed in healthy women compared to breast cancer patients.